1989
DOI: 10.1109/58.19148
|View full text |Cite
|
Sign up to set email alerts
|

SAW focusing by circular-arc interdigital transducers on YZ-LiNbO/sub 3/

Abstract: Using the angular spectrum theory and experimental velocity data of surface acoustic waves (SAW) on YZ-LiNbO(3), the focusing characteristics of a circular-arc interdigital transducer have been demonstrated. The calculated results show that the depth of focus is long and the compressed acoustic beam width is very narrow. The concept of a caustic is shown to be an excellent way of characterizing SAW focusing by a circular-arc interdigital transducer on YZ-LiNbO(3). Comparison between theoretical and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…17,18 Recent studies have indicated that SAW devices with focused interdigital transducers can be used to excite waves with high intensity, high beam-width compression ratio, and small localized area. [19][20][21][22] These high amplitude waves can be utilized to increase the induced streaming velocities to facilitate micromixing and microtransport. Similarly, acoustically focused two dimensional micromachined microdroplet ejector arrays fabricated on piezoelectric substrates were able to achieve formation of focal point by leaky SAWs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Recent studies have indicated that SAW devices with focused interdigital transducers can be used to excite waves with high intensity, high beam-width compression ratio, and small localized area. [19][20][21][22] These high amplitude waves can be utilized to increase the induced streaming velocities to facilitate micromixing and microtransport. Similarly, acoustically focused two dimensional micromachined microdroplet ejector arrays fabricated on piezoelectric substrates were able to achieve formation of focal point by leaky SAWs.…”
Section: Introductionmentioning
confidence: 99%
“…We also fabricate curved-electrode transducer that allow focussing of the SAW, thus providing a means for increasing the intensity of the SAW [9], [10], [11]. Without an absorbing gel on the edges of the substrate, a strong standing SAW is generated on the substrate when high excitation power was applied to the bi-directional IDT, thus providing a convenient mechanism for determining the exact location of the patterns formed by the deposited particles, whether at the nodal or antinodal positions.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Circular-arc IDTs were used in refs. [163,164] for SAW focusing. SH and in-plane waves in a half-space due to the excitation by a surface strip were analyzed in refs.…”
Section: Device-related Resultsmentioning
confidence: 99%